Hyperprogression to camrelizumab in a patient with esophageal squamous cell carcinoma harboring EGFR kinase domain duplication - Mei Wang; Meihong Wu; Minglu Liu; Zhengqing Yan; Guoqiang Wang; Dongliang Mao (Journal for ImmunoTherapy of Cancer)
Background Previous studies have reported that the amplification of some genes, such as Murine Double Minute 2 or 4 and Epidermal Growth Factor Receptor (EGFR), may be related to hyperprogressive disease (HPD). Exploring somatic gene alterations might be an effective method to predict HPD. Herein we characterize the somatic alterations in a patient with esophageal squamous cell carcinoma (ESCC) who developed HPD to investigate the potential origins of HPD.Case presentation A man in his mid-40s was diagnosed with ESCC. After the failure of first-line treatment with cisplatin and docetaxel, the patient participated in a phase III randomized, open, multicenter clinical trial (CTR20170307) and subsequently received camrelizumab. After 4 weeks of immunotherapy, the tumor size increased by 79% compared with baseline imaging; the progressive pace was 2.5-fold higher than preimmunotherapy, and a new liver metastasis appeared. A rare EGFR exon 2–28 duplication was discovered in both preimmunotherapy and postimmunotherapy tumor tissues.Conclusion This is the first report on a patient with ESCC harboring rare EGFR kinase domain duplication in exons 2–28 and developing HPD in the process of camrelizumab treatment. This case suggested that EGFR kinase domain duplication might be associated with HPD. Administration of immune checkpoint inhibitor monotherapy in this subgroup of patients harboring EGFR kinase domain duplication should be performed with caution. These results need to be further confirmed in a larger cohort of patients.